Hyperuricaemia in patients with gout - Majdan, Maria (Lekarz POZ, 2018)
In the article the current principles of diagnosis and treatment of hyperuricaemia and gout are presented. The questions frequently asked by family doctors are answered and the responses are thoroughly discussed.